Armonía de las jerarquías (2017)
"From the site analysis was concluded that the Caracas avenue creates a hierarchical relationship from the east over the west. Besides another factors are taken into account such as the responsibility of a proper response looking towards the future metro line that will be built in Bogota, and the borning Bogota art district in the neighborhood San Felipe. For those reasons the northwest corner of the intersection between the av. caracas and the 72th street was chosen. The project's main idea is to abolish the physical and social hierarchies through music. In the practice that means a program which could be able to create community by means of the sharing of music: a school and a concert hall... Acoustically the challenge of the project was substantial because of the location in a street where a lot of noise is going to be expected, therefore a lot of decisions where made taking into account this requirements.." -- Tomado del Formato de Documento de Grado.